A basic ddRADseq two‐enzyme protocol performs well with herbarium and silica‐dried tissues across four genera. (23rd April 2020) - Jordon‐Thaden, Ingrid E.; Beck, James B.; Rushworth, Catherine A.; Windham, Michael D.; Diaz, Nicolas; Cantley, Jason T.; Martine, Christopher T.; Rothfels, Carl J.
Abstract : Premise: The ability to sequence genome‐scale data from herbarium specimens would allow for the economical development of data sets with broad taxonomic and geographic sampling that would otherwise not be possible. Here, we evaluate the utility of a basic double‐digest restriction site–associated DNA sequencing (ddRADseq) protocol using DNAs from four genera extracted from both silica‐dried and herbarium tissue. Methods: DNAs from Draba, Boechera, Solidago, and Ilex were processed with a ddRADseq protocol. The effects of DNA degradation, taxon, and specimen age were assessed. Results: Although taxon, preservation method, and specimen age affected data recovery, large phylogenetically informative data sets were obtained from the majority of samples. Discussion: These results suggest that herbarium samples can be incorporated into ddRADseq project designs, and that specimen age can be used as a rapid on‐site guide for sample choice. The detailed protocol we provide will allow users to pursue herbarium‐based ddRADseq projects that minimize the expenses associated with fieldwork and sample evaluation.